Colloidal CdxZn1−xS nanocrystals as efficient photocatalysts for H2 production under visible-light irradiation. Issue 7 (30th January 2019) - Xiang, JingJing; Wang, Hanbin; Wang, Xina; Chen, Xu; Wu, Tianci; Wan, Houzhao; Liu, Yongzheng; Wang, Hao
Abstract : Colloidal Cd x Zn1− x S and Pt–Cd x Zn1− x S nanocrystals by simple organic solution method show efficient photocatalytic H2 -evolution performance. Abstract : Cd x Zn1− x S nanocrystals with sizes ranging from 3–11 nm were synthesized by a simple organic solution method. The nanocrystals possess a cubic zinc-blende structure and the bandgap blue-shifts from 2.1 eV to 3.4 eV by increasing the composition of Zn ions in the solid solutions. After a facile ligand exchange process, the photocatalytic activity for H2 production of the Cd x Zn1− x S nanocrystals was investigated under visible-light irradiation ( λ ≥ 420 nm) with Na2 SO3 /Na2 S as the electron donor. It was found that the Cd0.8 Zn0.2 S had the highest photoactivity with H2 evolution rate of 6.32 mmol g −1 h −1 . By in situ adding Pt precursors into the reaction solution, inhomogenous Pt–Cd x Zn1− x S nanoheterostructures were formed, which accounted for a 30% enhancement for the H2 evolution rate comparing with that of pure Cd0.8 Zn0.2 S nanocrystals. This work highlights the use of facile organic synthesis in combination with suitable surface modification to enhance the activity of the photocatalysts.